Crime and social control in pandemic times - Deflem, Mathieu (Sociology of crime, law and deviance ;, 2023)
Theoretically and methodologically diverse, Volume 28 of Sociology of Crime, Law and Deviance addresses important questions of crime, punishment, policing, social control, and law in relation to COVID-19. The pandemic has brought about a wide number of analyses from various viewpoints, but what role has the study of crime, deviance, and social control played? A timely contribution that tackles a variety of related topics and brings together authors from a range of social-science disciplines, Crime and Social Control in Pandemic Times is a diverse and useful resource for those interested in the dynamics of crime and social control at a time of huge global disruption.